Pengaruh Pendapatan Asli Daerah dan Dana Perimbangan Terhadap Kinerja Keuangan Pemerintah Daerah Kabupaten/Kota di Provinsi Jambi Tahun 2018-2021 - Ari Nugroho; Yuliusman Yuliusman; Riski Hernando (JAKU (Jurnal Akuntansi & Keuangan Unja) (E-Journal), 2023)
This research is entitled The Effect of Regional Original Income and Balancing Funds on the Financial Performance of District and City Governments in Jambi Province in 2018–2021. The population of this study is the district and city local governments in Jambi Province in 2018–2021. The sampling technique uses purposive sampling, where the sample is determined based on what is determined. In line with that, there are 9 districts or cities in Jambi Province where samples were taken for 4 years. in order to obtain 36 observational data points. The data in this research is secondary data. The data analysis tool used in this study was the SPSS version 24 program. The results showed that local revenue had a positive and significant effect on regional government financial performance, and balancing funds had a significant effect on regional government financial performance.